Rancang Bangun Website BUMDes Kabupaten Cilacap Menggunakan Metode Scrum - Tazakka Pribadi, Fadhil; Intan Surya Saputra, Dhanar (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2026)
Libraries play a crucial role in broadening the public's knowledge horizons by improving literacy skills. However, the reality at the Samaturu Library in Jambu Malea Village shows that manual management still dominates, leading to various administrative obstacles such as data irregularities, the risk of losing important information, and inefficiencies in tracking daily activities. This condition demands digital transformation to optimize public services at the village level comprehensively and sustainably. This research focuses on the development of a web-based library information system specifically designed to modernize administrative processes to be more systematic, fast, and organized. Built using the PHP programming language and MySQL database, this platform offers an intuitive interface for both staff and members. Its superior features include book data management, membership, activity agendas, announcements, and digitizing the borrowing and return process. Furthermore, the system is capable of automatically generating periodic reports to facilitate library performance evaluation. Based on the results of comprehensive testing using the Black Box Testing method, all system functionality was proven to operate optimally according to the required specifications. Direct user trials also showed very positive responses regarding aspects of ease of navigation and operational time efficiency. The implementation of this system is expected to improve the effectiveness of internal management, accelerate the quality of services to library users, and become a major catalyst in realizing superior digital literacy governance in rural areas.